2020
DOI: 10.1186/s40814-020-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Training attention control of very preterm infants: protocol for a feasibility study of the Attention Control Training (ACT)

Abstract: Background: Children born preterm may display cognitive, learning, and behaviour difficulties as they grow up. In particular, very premature birth (gestation age between 28 and less than 32 weeks) may put infants at increased risk of intellectual deficits and attention deficit disorder. Evidence suggests that the basis of these problems may lie in difficulties in the development of executive functions. One of the earliest executive functions to emerge around 1 year of age is the ability to control attention. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…In addition, some recent studies have shown that early training of attentional control in infancy can have short-term effects on emergent EF 42,74,75 . Therefore, it is possible that interventions including oculomotor response shifting tasks, especially those which involve inhibiting perseverative www.nature.com/scientificreports/ looking, have positive effects on the subsequent neurobehavioural development in preterm children 76 . Given the potential cascade of early negative effects on neurobehavioural outcomes in high-risk preterms 71,77 , it is important to consider whether such intervention reduces the risk of long-term executive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some recent studies have shown that early training of attentional control in infancy can have short-term effects on emergent EF 42,74,75 . Therefore, it is possible that interventions including oculomotor response shifting tasks, especially those which involve inhibiting perseverative www.nature.com/scientificreports/ looking, have positive effects on the subsequent neurobehavioural development in preterm children 76 . Given the potential cascade of early negative effects on neurobehavioural outcomes in high-risk preterms 71,77 , it is important to consider whether such intervention reduces the risk of long-term executive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would be consistent with transdiagnostic, process-focused research into early markers of neurodevelopmental disorders and child psychopathology. As an example, some have begun to test whether attention training among infants at risk for disrupted attentional processing (i.e., infants at familial risk for ADHD, infants at familial risk for ASD, infants who are born preterm) is feasible and effective (Forssman & Wass, 2018;Goodwin et al, 2016;Perra et al, 2020). These types of mechanisms-or process-focused approaches have shown initial evidence of generalizability to non-trained dimensions such as social communication among infants who are JOURNAL OF CLINICAL CHILD & ADOLESCENT PSYCHOLOGY not at known risk, at least in the short term (Forssman & Wass, 2018).…”
Section: Expanding the Scope And Delivery Of Targeted Interventions Fmentioning
confidence: 99%
“…The majority of the included studies are described in this section (14/24). In particular, ET-based training programs were developed to address the following populations: typically developing infants [ 44 , 45 ]; infants at familial risk for ADHD [ 41 ] or with an overt diagnosis of ADHD [ 30 , 31 , 37 , 42 ]; children with RS [ 34 , 35 , 39 ]; children with ASD [ 25 , 36 ]; and very preterm infants [ 40 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Attention Control Training proposed by Perra and colleagues [ 40 , 49 ] employed three types of tasks, presented by means of interactive cartoons, in order to train the following abilities: search for a target among distractors; visual short-term memory for objects embedded in scenes; and maintaining a goal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation